1998
DOI: 10.1159/000012277
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral Functioning of Adults with Pituitary Disease

Abstract: Neurobehavioral disorders are not infrequent in adults with pituitary disease. The disorders can be due to compression of brain structures important for cognitive and emotional function, effects of hormonal imbalance on sensitive structures, post-surgical disruption of connecting pathways, adverse reactions to medical therapy, and adverse delayed effects of radiation therapy. A multidisciplinary team approach to the treatment of pituitary tumors will allow for the early diagnosis of neurobehavioral disorders a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The effects of tumor compression on the third ventricle and diencephalic structures has been described previously and even amnestic syndromes in patients harbouring large adenomas with suprasellar extension and invasion of the diencephalon as part of the clinical spectrum have been reported. 5,23 In patients with non-functioning adenomas, we could show clearly in the multivariate analyses that improvement of overall concentration, as shown by psychomotor speed, could be best explained by successful removal of the suprasellar portion of the tumor. This finding applied to not only patients with non-functioning adenomas, but also to patients harbouring prolactinomas or other sellar lesions.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The effects of tumor compression on the third ventricle and diencephalic structures has been described previously and even amnestic syndromes in patients harbouring large adenomas with suprasellar extension and invasion of the diencephalon as part of the clinical spectrum have been reported. 5,23 In patients with non-functioning adenomas, we could show clearly in the multivariate analyses that improvement of overall concentration, as shown by psychomotor speed, could be best explained by successful removal of the suprasellar portion of the tumor. This finding applied to not only patients with non-functioning adenomas, but also to patients harbouring prolactinomas or other sellar lesions.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, we assume that patients harbouring macroadenomas with suprasellar tumor extension, either functioning or not, profit from the decompression of adjacent neuroanatomical structures. 5,23 In patients with acromegaly, improvements in concentration performance and psychomotor speed were not correlated with the preoperative suprasellar extension. However, only 37% of patients with acromegaly presented with an initial suprasellar tumor extension.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…To obtain an actual advancement of psychosomatic and psychiatric research, overcoming the rigid dichotomy between psychological and biological processes is mandatory [202]. In the same way, significant progress in the understanding of endocrine diseases requires endorsement of a biopsychosocial approach [203, 204, 205, 206, 207, 208, 209, 210]. …”
Section: Discussionmentioning
confidence: 99%
“…Although there were cognitive differences between both pituitary groups and controls, there were no differences between the irradiated and nonirradiated groups. Additional studies (Meyers, 1998;Peace et al, 1997) identified memory and executive impairments from the effects of pituitary tumors, and attributed these impairments to radiation therapy, hormone imbalance, and surgery. Rarely have other deep tumor studies, specifically meningiomas in the falx or cavernous sinus, found neuropsychological effects (Ledakis, Jo, Armstrong, & Hunter, submitted).…”
mentioning
confidence: 99%